EFEKTIVITAS KINERJA DEWAN PENGAWAS SYARIAH PADA BANK PEMBIAYAAN RAKYAT SYARIAH DI SUMATERA BARAT - Khalieda, Fatma (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
Abstract : The main function of supervision of DPS in Sharia Banks as mandated in the law is to support the efforts to realize a sound sharia banking, operate prudently, and meet the prevailing provisions to protect the interests of customers. This study was appointed to analyze whether the performance of Sharia Supervisory Board in terms of supervision based on Bank Indonesia Circular Letter no. 15/22 / DPbS Year 2013 on Guidelines for Implementation of Duties and Responsibilities of Sharia Supervisory Board The Shariah Financing Bank has been running effectively. The research method used is descriptive qualitative research. In this study, the case study is 3 BPRS located in West Sumatra. The type of data used is the primary data from questionnaires and interviews with DPS. The results of this study indicate that the implementation of supervision of DPS in three BPRS based on Bank Indonesia Circular Letter no. 15/22 / DPbS Year 2013 on Guidelines for Implementation of Duties and Responsibilities of Shariah Supervisory Board of Sharia Rural Bank based on the questionnaire results, it is found that the average score of 4.21 indicates that the performance of DPS has been very effective while based on interviews with DPS there are several things that make the DPS task has not fully run effectively because there are some things supervision done DPS has not meet the indicators of effectivenessKeywords : Sharia Supervisory Board, Effectiveness, Performance and Supervision